Historical and Archival Aspects of Expertise and Attribution of N. K. Roerich’s Works - Yakovleva, Elena P. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
Based on the materials of expert and attribution studies carried out by the author over the years, this article examines the historical and archival documents, evidence and facts used in the course of the examination and attribution of works of easel, theatrical and decorative art of Nicholas Roerich (1874–1947). Also, the author examines the role which documents from the funds of the departments of manuscripts of the State Russian Museum, the State Tretyakov Gallery, the Russian State Archives of Literature and Art, the Central State Archive of Film and Photographic Documents of St Petersburg, and other institutions play in the examination process, which is important for clarifying and studying the artistic heritage of the master. The purpose of the article is to consider individual examples of the examination and attribution of N. K. Roerich’s works with the help of various kinds of historical, cultural, and everyday documents, facts, and evidence reflected in unpublished art history texts, epistolary and memoir sources, in inscriptions on the reverse of paintings and on the margins of typographic prints of exhibition catalogues and works of art by Roerich, i.e. everything that contains important information for an expert included in the concept of “historical and archival aspects”. The article provides examples of art history, culturological and technical and technological methods used in the examination and attribution of works of art, and their result, which is reflected in the “expert conclusions”, attributions, verified and refined description of works and the history of their existence, which is important for understanding the artist’s work, further analysis of his work and, as a result, the emergence of new scholarly and educational publications.